Comparison of ultrasonographic features between two types of hepatic echinococcosis and hepatoblastoma in children - Tao, Yi; Kong, Hanqing; Li, Jiawu; Tan, Zhizhi; Wang, Jun; Luo, Yan (Frontiers in Pediatrics, 2025)
IntroductionThe prevalence of hepatic alveolar echinococcosis (AE) and cystic echinococcosis (CE) is notably high among children in western China, with the mortality rate for untreated children potentially reaching up to 90%. Meanwhile, hepatoblastoma is the most common malignant liver tumor in children, yet its treatment differs significantly from that of hepatic echinococcosis. This study aimed to compare and analyze the ultrasonographic and contrast-enhanced ultrasound (CEUS) characteristics of hepatic CE, AE, and hepatoblastoma in children, providing more imaging evidence for accurate clinical diagnosis.MethodsA retrospective analysis was conducted on preoperative data from children with pathologically confirmed hepatic echinococcosis in our hospital between 2012 and 2024. Furthermore, children consecutively diagnosed with hepatoblastoma between 2020 and 2024, confirmed by histopathological examination, were selected as the control group. Clinical data, conventional ultrasound images, and CEUS characteristics of hepatic echinococcosis and hepatoblastoma were analyzed and compared.ResultsThe mean ages of 22 children with hepatic CE and nine children with hepatic AE were 11.6 ± 2.8 years and 11.8 ± 3.6 years, respectively. The mean age of 36 children with hepatoblastoma was 2.9 ± 3.0 years. Significant differences were observed in age and history of residence or travel to endemic areas among children with hepatic echinococcosis and hepatoblastoma (P < 0.001). Hepatic CE and hepatoblastoma showed a higher proportion of cystic degeneration [≥50% (54.5%, 12/22), and between 0% and <50% (47.2%, 17/36, respectively)], while hepatic AE predominantly showed no cystic degeneration (88.9%, 8/9). Clear boundaries were most commonly seen in hepatic CE lesions (95.5%, 21/22), while unclear boundaries were more frequent in hepatic AE lesions (88.9%, 8/9) (P < 0.05). Calcification was more prevalent in hepatic AE compared to hepatic CE and hepatoblastoma (P < 0.05). Hepatoblastoma exhibited richer color Doppler signals (94.4%, 34/36) compared to hepatic CE and AE (P < 0.05). CEUS was performed on two hepatic echinococcosis and nine hepatoblastoma lesions. On CEUS, one hepatic AE lesion showed peripheral hyperenhancement in the arterial phase, while one hepatic CE lesion showed no significant enhancement. In hepatoblastoma, nine lesions demonstrated hyperenhancement in the arterial phase and hypoenhancement in the late phase.ConclusionThis study demonstrates the value of ultrasound in differentiating hepatic echinococcosis from hepatoblastoma in children. Hepatic CE typically manifests as a well-defined cystic or cystic-solid mass, while hepatic AE often presents as an ill-defined cystic-solid or solid mass with diffuse calcifications. Conversely, hepatoblastoma appears as a partially well-defined cystic-solid or solid mass with abundant color Doppler signals within and around the lesion.